A bill to amend several acts of the General Assembly, in relation to the Deaf, and Dumb, and the Blind ([Seaton Gales, printer to the Legislature], 1852)
1852 Senate bill to amend the Deaf, Dumb and Blind Act, proposed by the Joint Select Committee on the Condition of the Institution for the Deaf, Dumb and Blind and issued with their report. The bill increased the term for a tax from four to seven years; annually appropriated $8,000 for the renamed The North Carolina Institution for the education of Deaf, and Dumb, and of the Blind; and appropriated $7,500 for additions and a principal's residence.